The Implication of Law No. 11 of 2020 concerning Job Creation towards Regulation on the Permit to Open Land State in East Kalimantan - Mohamad Nasir (Pusjar SKPP Lembaga Administrasi Negara, 2021)
Four regions in East Kalimantan province, including Balikpapan, Kutai Kartanegara, Penajam Paser Utara, and Samarinda, have local regulations known as Perda concerning the permission to open land state (IMTN). As a licensing instrument, IMTN has closely related to other sectors, such as investment, public services, and regional government. The policy's dynamics and changes in those sectors will impact the land sector, including the IMTN regulation. This article aims to examine two issues. First, the status of IMTN norms in licensing law regimes. Second, the conformity of the Perda along with the development of the higher regulations. In particular, the implication of Law No. 11/2020 to Perda IMTN in East Kalimantan and formulate alternative solutions to address the dynamics of land policy at the national level. This research applies normative legal analysis (doctrinal) to examine the relationship between norms within related regulations. This paper reveals that IMTN norms in licensing law regimes are unclear. De jure is a permit, and it means that IMTN should be given before the activities to open state land are conducted (constitutive). De facto, IMTN has more value as an instrument to reaffirms the existing land (declarative). Thus, for its relation to higher regulations, the Perda has not accommodated some provisions on administrative efforts as stipulated in Law No. 30/2014, complaint management as mandated by Law No. 25/2010, and the risk-based approach in business licensing as introduced by Law No. 11/2020. Therefore, Perda on IMTN should be amended or replaced to adjust to higher regulations' norms.